2017
DOI: 10.1002/app.45919
|View full text |Cite
|
Sign up to set email alerts
|

Development of sericin/alginate particles by ionic gelation technique for the controlled release of diclofenac sodium

Abstract: Sericin and alginate particles, prepared by ionic gelation technique, demonstrated to be a promising matrix to controlled release of diclofenac sodium. Ten particle compositions of sericin, alginate, and diclofenac were evaluated. The drug incorporation was confirmed by scanning electron microscopy, Fourier Transform Infrared Spectroscopy, and X‐ray diffraction analysis. In vitro dissolution profile was performed to obtain the drug release profile in gastric and enteric medium. The drug release profile indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 57 publications
3
7
0
3
Order By: Relevance
“…With electrical stimuli, the releases were accelerated but were still nicely fitted by Higuchi Equation X =k1 t0.5where X is the fractional drug release, k 1 is a kinetic constant, and t is the release time, with the kinetic parameters increased from 0.0815 to 0.1425 for MB and from 0.0676 to 0.1386 for SF. The releases of the zwitterionic RhB and the peptide could only be well fitted using the first‐order equation shown as formula ln1X=k2 twhere X is the fractional drug release, k 2 is a kinetic constant, and t the release time, indicating that the interactions between the releasing molecules and the matrix dominated the release processes (Figure S5c,d,g,h, Supporting Information). The kinetic parameters increased from 0.0244 to 0.0667 for RhB without and with electrical stimuli, and from 0.0165 to 0.0577 for the peptide, again demonstrating apparent release accelerations by the piezoelectrical fields.…”
Section: Resultsmentioning
confidence: 99%
“…With electrical stimuli, the releases were accelerated but were still nicely fitted by Higuchi Equation X =k1 t0.5where X is the fractional drug release, k 1 is a kinetic constant, and t is the release time, with the kinetic parameters increased from 0.0815 to 0.1425 for MB and from 0.0676 to 0.1386 for SF. The releases of the zwitterionic RhB and the peptide could only be well fitted using the first‐order equation shown as formula ln1X=k2 twhere X is the fractional drug release, k 2 is a kinetic constant, and t the release time, indicating that the interactions between the releasing molecules and the matrix dominated the release processes (Figure S5c,d,g,h, Supporting Information). The kinetic parameters increased from 0.0244 to 0.0667 for RhB without and with electrical stimuli, and from 0.0165 to 0.0577 for the peptide, again demonstrating apparent release accelerations by the piezoelectrical fields.…”
Section: Resultsmentioning
confidence: 99%
“…Desenvolvimento da blenda: Para a preparação da blenda de sericina e alginato foi realizado método similar ao proposto por Vidart et al (2018). Para isso, a solução de sericina com a concentração já ajustada passou por um processo de re-aquecimento em autoclave a 120 ºC e à pressão de 1 kgf/cm 2 , por 10 min.…”
Section: Parte Experimentalunclassified
“…Preparação das partículas: Para a obtenção das partículas, as soluções contendo o fármaco passaram pelo processo de gelificação iônica (Vidart et al, 2018), no qual a solução foi gotejada em solução de cloreto de cálcio (CaCl2) 3% sob agitação magnética, para que a gelificação ocorresse de forma instantânea. Após esta etapa as partículas foram colocadas sob agitação em jar test a 100 rpm durante 30 min, com o objetivo de completar a reticulação.…”
Section: Parte Experimentalunclassified
See 1 more Smart Citation
“…Diclofenac sodium (DS) is a nonsteroidal anti-inflammatory drug, and is used to treat soft tissue injury due to its effectiveness and safety [ 1 , 8 , 9 ]. Studies have demonstrated that DS could penetrate the skin and distribute to the target tissue underlying the application site [ 8 , 10 , 11 ]. Generally, the commercially available DS is DS ointment, which cannot control the release of the drugs, resulting in dose-dependent problems, such as gastrointestinal, dermatological and the central nervous system toxicity [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%